Primer of biostatistics - Glantz, Stanton A. (New York McGraw-Hill, Medical Pub. Div., 2011)
The new fifth edition of Primer of Biostatistics introduces this challenging topic in a readable and enjoyable format that assumes no prior knowledge of the subject. In no time, you'll understand test selection and be able to evaluate biomedical statistics critically and knowledgably.
Ch. 1. Biostatistics and clinical practice -- Ch. 2. How to summarize data -- Ch. 3. How to test for differences between groups -- Ch. 4. The special case of two groups: the t test -- Ch. 5. How to analyze rates and proportions -- Ch. 6. What does "not significant" really mean? -- Ch. 7. Confidence intervals -- Ch. 8. How to test for trends -- Ch. 9. Experiments when each subject receives more than one treatment -- Ch. 10. Alternatives to analysis of variance and the t test based on ranks -- Ch. 11. How to analyze survival data -- Ch. 12. What do the data really show?
Includes bibliographical references and index.
Keywords: Medical statistics; Biometry